The nursing assistance under a sistemátic way to care young diabetic focusing on the self-care - Wandecleide Lucena Fernandes; João Modesto Filho; Maria Míriam Lima da Nóbrega (Rev Rene)
The purpose of produce the nursing assistance to patient with insulin-dependent Diabetes Mellitus by using the self-care theory by OREM, we used in this resent a qualitative methodology, and the approach technique was the case study, by applying the partially structured interview. The sample was made by male young patients insulin-dependent Diabetes Mellitus. They were attended in endocrinology services from public and private health services during a 6-month-period. We applied the self-care theory by OREM in two diabetics women with data survey, diagnosis and care planning. It was concluded that the obtained results could contribute as a reference for a diabetic-assistance model. It was concluded also that the nurse could evaluate his assistencial practice in more critical form, when he applies the nursing process to diabetic patients with the theory by OREM. It is recommended this model to be adopted in public services in order to the self-care, by using an administrative politics that stimulates this practice.